Alceu Valença na ditadura militar: uma análise discursiva dos seus primeiros discos. - Lima, Júlio de Oliveira (2021)
Alceu Valença is one of the most famous artists from Pernambuco, Brazil. He made fame with romantic songs such as "Morena Tropicana", but he started his career long before, in a moment of great political tension in the country. Those were some of the hardest years of the Military Dictatorship in Brazil. We have analysed in this work, using the theory and method of the French Discourse Analysis, founded by Michel Pêcheux, the three first albuns of Alceu Valença in its visual, musical and verbal aspects, considering that cover, audio and lyrics constitute an effect of totality (TRAJANO, 2017) that must be taken into account on the analysis. Moved by the hypothesis that his works produced the effect of confronting the Dictatorship, we have investigated how the resistance to the ideological interpellation took place on his songs; we have identified the effects of the silence policies (ORLANDI, 2007); we have investigated the tension between paraphrastic process (what is kept) and polissemical process (the displacement); we also identified the use of discursive strategies, such as the excess and the absence (ERNST-PEREIRA, 2009) in his songs and the sense effects that those strategies produce; we have identified two discursive formations to which the author subscribes in some of his songs. Our hypothesis has been confirmed over the analysis, in songs such as "Sol e Chuva", in which the author brings the love discourse to talk about the political (ORLANDI, 2007) and "Você Pensa", in which he produces the effect of critics to the normalization of the individuals.